Riding the wave of BYOD: developing a framework for creative pedagogies - Thomas Cochrane; Laurent Antonczak; Helen Keegan; Vickel Narayan (Association for Learning Technology, 2014)
Moving innovation in teaching and learning beyond isolated short-term projects is one of the holy grails of educational technology research, which is littered with the debris of a constant stream of comparative studies demonstrating no significant difference between innovative technologies and traditional pedagogical approaches. Meanwhile, the approaching giant wave of the bring your own device (BYOD) movement threatens to overwhelm education practitioners and researchers preoccupied with replicating current practice on mobile devices. A review of the literature indicates that there are yet few well-developed theoretical frameworks for supporting creative pedagogies via BYOD. In this paper, we overview the development of a framework for creative pedagogies that harness the unique affordances of BYOD. This framework has been used across multiple educational contexts and scale from short workshops through to full courses and international collaborative projects. Our key design principles for supporting creative pedagogies via BYOD include modelling collaborative practice via establishing teacher communities of practice to learn about the affordances of mobile devices in relation to new modes of student learning, collaborative curriculum redesign in response to shifts in conceptions of teaching and learning, and collaborating with ICT Services for infrastructure development across the campus.